Bridging psychological barriers between the child and the father after his returning from the war – Could group art therapy help? - Mandić Gajić, Gordana (Vojnosanitetski pregled, 2017)
Introduction. War veterans　with chronic post-traumatic stress disorder (PTSD) have poorer family and parenting functioning, but little research has focused on these impairments. Case report. This paper presented how the series of drawings and the group art therapy process enhanced bridging the psychological barriers of a 33-year-old male PTSD war veteran to engagement with the child. After two years of deployment he returned home and suffered mostly from PTSD numbness and avoidance symptoms. The veteran had the family readjustment difficulties and felt guilty for being detached from his 3-year-old son. He underwent integrative treatment in the Day Unit Program. The drawings series were made by free associations. Clinical observations and group discussions were recorded in the group art therapy protocols. The presented patient got gratifications and support from the group members for his illustration of popular cartoon heroes, and decided to draw Mickey Mouse at home. On the next session he shared his satisfaction for bridging the gap between him and his son, having done the same drawings with his son at home. Beck's depression inventory (BDI) was used for self-rating of depression and a reduction of BDI score from 18 to 6 during the treatment course was recorded. Conclusions. Series of drawings illustrated shift from war related past toward current family life of the war veteran. Group art therapy gave him gratification and support with hope and a sense of belonging, thus facilitated his parenting readjustment.
Keywords: stress disorders; post-traumatic; war; family; parent-child relations; art therapy